The Fear of Contagion and the Attitude Toward the Restrictive Measures Imposed to Face COVID-19 in Italy: The Psychological Consequences Caused by the Pandemic One Year After It Began - Rania, Nadia; Coppola, Ilaria (Frontiers in Psychology, 2022)
The pandemic nature of COVID-19 has caused major changes in health, economy and society globally. Albeit to a lesser extent, contingent access to shops and places to socialize, the imposition of social distancing and the use of indoor masks are measures still in force today (more than a year after the start of the pandemic), with repercussions on economic, social and psychological levels. The fear of contagion, in fact, has led us to be increasingly suspicious and to isolate ourselves from the remainder of the community. This has had repercussions on the perception of loneliness, with significant psychological consequences, such as the development of stress, anxiety and, in extreme cases, depressive symptoms. Starting from these assumptions, this research, with a multidisciplinary approach, was developed with the aim of deepening the perceptions that the participants have of their own mental health, loneliness, fear linked to contagion and attitudes toward imposed social distancing. In particular, we wanted to analyze whether there is a relationship between perceived fear and the perceived level of mental health, loneliness and attitude toward social distancing. Finally, we wanted to analyze whether there are differences related to gender, age, marital status, current working mode and educational qualifications. The research, performed after the diffusion of the vaccination in Italy, lasted 14 days. The participants were 500 Italians who voluntarily joined the study and were recruited with random cascade sampling. The research followed a quantitative approach. The analyzed data, from participants residing throughout the national territory, allow us to return the picture of the perceptions that Italians have of the fear of contagion, of their level of mental health, of loneliness and of their attitude toward social distancing. In particular, the data show that fear of COVID-19 is an emotional state experienced by the entire population and that young people have suffered more from loneliness and have been less inclined to accept the imposed social distancing. The data that emerged should make policymakers reflect on the need to find functional strategies to combat COVID-19 or other health emergency crises whose effects do not affect the psychological well-being of the population.